2011
DOI: 10.1038/eye.2011.242
|View full text |Cite
|
Sign up to set email alerts
|

In-the-bag scleral suturing of intraocular lens in eyes with severe zonular dehiscence

Abstract: PurposeTo compare the degree of tilt and decentration of an intraocular lens (IOL), refractive status, and prediction error between eyes that underwent trans-scleral suturing of the IOL within the capsular bag (in-the-bag scleral suturing) and eyes that underwent scleral suturing outside of the bag (out-of-the-bag scleral suturing) because of severe zonular dehiscence.Patients and methodsThirty eyes that underwent in-the-bag scleral suturing of an IOL and 38 eyes that underwent out-of-the-bag scleral suturing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Hayashi K's study showed that the tilt and decentration of the IOL after out-of-the-bag implantation were significantly greater than those after in-the-bag implantation, and the extent of both tilt and decentration after scleral suture fixation was greater than that observed after either out-ofthe-bag or in-the-bag implantation [19,20], which was consistent with part of our findings. In comparison with data in the published literature, our study showed that the tilt of the IOL after trans-scleral fixation in CEL patients was not significantly greater than that after in-the-bag implantation in cataract patients, whereas the decentration of the IOL in CEL patients was significantly greater [21].…”
Section: Discussionsupporting
confidence: 89%
“…Hayashi K's study showed that the tilt and decentration of the IOL after out-of-the-bag implantation were significantly greater than those after in-the-bag implantation, and the extent of both tilt and decentration after scleral suture fixation was greater than that observed after either out-ofthe-bag or in-the-bag implantation [19,20], which was consistent with part of our findings. In comparison with data in the published literature, our study showed that the tilt of the IOL after trans-scleral fixation in CEL patients was not significantly greater than that after in-the-bag implantation in cataract patients, whereas the decentration of the IOL in CEL patients was significantly greater [21].…”
Section: Discussionsupporting
confidence: 89%
“…Retaining the haptics in the bag can stretch the capsular bag (especially toward the direction of zonulysis) according to the total length of the planned IOL. In traditional sulcus scleral fixation methods, total capsular phimosis or bag shrinkage or bag distortion can be caused by an absence of the IOL haptics in the bag [29][30][31] . This technique can also prevent total capsular phimosis or bag shrinkage due to an absence of the IOL haptics as seen in traditional scleral sulcus fixation.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is necessary to observe the patient postoperatively for unstable fixation, such as IOL inclination. 15 , 16 …”
Section: Discussionmentioning
confidence: 99%